Analysis of the Application of Environmental Accounting to Realize Sustainable Development Goals from an Islamic Perspective - Ahmed, Zakaria; Yenni Samri Juliati Nasution; Nurlaila (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This research aims to analyze the implementation of environmental accounting in the management of Swiss gomara tourism in Simonis Village and its relation to the achievement of sustainable development goals (SDGs) from an Islamic perspective. Unenvironmentally friendly tourism activities such as waste accumulation will threaten the sustainability of ecosystems. This study uses a qualitative approach through observation, interviews, and documentation. The results of this study indicate that environmental accounting has been applied, but not optimally in its management. The management has not fully realized the importance of SDGs in tourism operations. The integration of Islamic principles such as Muhafazzah 'ala al-biah and khalifah fil ardh is considered to strengthen the management of tourism. This implementation is expected to encourage the achievement of the SDGs, particularly SDG 6 (Clean Water and Sanitation) and 15 (Life on Land). Through the synergy of managers, communities, and the government, sustainable and environmentally friendly tourism can be created.